Uncommon accountability : a radical new approach to greater success and fulfillment - Moran, Brian, 1959-; Lennington, Michael, 1958- (John Wiley & Sons, Inc., 2022)
"Accountability is the bedrock upon which all lasting success is built. It is the necessary virtue for both individuals, and organizations, to realize their full potential. Accountability enables learning and growth, improves well-being, reduces stress, and drives results. But what if nearly everyone is wrong about the true nature of accountability? What if we have substituted something else it it's place, something that works to improve short-term results, but limits long term organizational health and success? What if the widespread management approach of "holding others accountable" instead of creating accountability, encourages blame, limits results and growth, inhibits risk-taking, generates fear, fosters workplace conflict, and lowers over-all health and well-being? Authors Brian Moran and Mike Lenngington make the argument for what accountability truly is -- personal ownership of ones goals, actions, and progress. They show individuals how to take personal ownership, and thereby change their circumstances. They will also show leaders how to stop managing by consequences through "holding others accountable," and instead start leading to ownership by "holding others capable." In this way can individuals and organizations deliver on what they are truly capable of."--